2016
DOI: 10.1136/vr.103609
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 10‐minute versus 30‐minute tourniquet time for intravenous regional limb perfusion with amikacin sulfate in standing sedated horses

Abstract: The objective of the article is to determine the synovial fluid concentrations of amikacin sulfate (AS) after performing an intravenous regional limb perfusion (IVRLP) with the tourniquet in place for 10 minutes and compare this with 30 minutes. This is a randomised crossover experimental design. Animals were seven healthy adult horses. Horses underwent two IVRLP procedures in a randomised, crossover design. The horses received IVRLP with 2 g AS diluted to 60 ml using 0.9% saline in the cephalic vein of altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 17 publications
1
37
2
Order By: Relevance
“…In a paper summarised on p 585 of this issue of Veterinary Record , Kilcoyne and others (2016) found no difference in synovial antimicrobial concentrations between 10- and 30-minute tourniquet application times. An additional study from the same laboratory found no significant difference in synovial antimicrobial concentration between horses having 20 and 30 minutes of tourniquet application during RLP (Aristizabal and others 2016).…”
Section: Duration Of Applicationmentioning
confidence: 97%
See 1 more Smart Citation
“…In a paper summarised on p 585 of this issue of Veterinary Record , Kilcoyne and others (2016) found no difference in synovial antimicrobial concentrations between 10- and 30-minute tourniquet application times. An additional study from the same laboratory found no significant difference in synovial antimicrobial concentration between horses having 20 and 30 minutes of tourniquet application during RLP (Aristizabal and others 2016).…”
Section: Duration Of Applicationmentioning
confidence: 97%
“…Furthermore, using a vein proximal to the carpus or tarsus is useful when the distal limb suffers from trauma since it allows for immobilisation of the region with a cast when indicated (Kelmer and others 2012). Recently, most RLP studies have used the cephalic vein and it appears that using the proximal vein is the preferred site for catheter placement (Beccar-Varela and others 2011, Zantingh and others 2014, Aristizabal and others 2016, Kilcoyne and others 2016, Oreff and others 2016, Sole and others 2016). …”
Section: Which Vein To Usementioning
confidence: 99%
“…The constant battle against resistant bacteria creates a growing need for the development of more efficient treatments. As a result, significant research effort has recently focused on RLP, such as investigating combinations of antimicrobials, the use of additional types of antimicrobials, and improving the technique …”
Section: Introductionmentioning
confidence: 99%
“…Little consensus exists regarding how IVRLP should be performed, which limits direct comparisons between studies and the ability to identify sources of variability. There is debate concerning the ideal technical aspects of the procedure (eg, tourniquet type and number, perfusate volume, perfusion time), and the available data are equivocal . The IVRLP performed here was intended to reproduce that easily performed by the general practitioner, and attempts were made to ensure consistency of the procedure and sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…Tourniquets are known to cause discomfort in man, so their use is predominantly restricted to anesthetized patients . Their use in minimally sedated horses can similarly result in painful responses, requiring the use of sedation . Tourniquet release is reportedly painful in human patients, and painfulness is also suspected in equine patients because of their repetitive limb movements after removal .…”
Section: Discussionmentioning
confidence: 99%